Sharp ill-posedness of the Dirac–Klein–Gordon system in one dimension. (March 2020) - Machihara, Shuji; Okamoto, Mamoru
Abstract: We show the ill-posedness of the Cauchy problem for the Dirac–Klein–Gordon system in one dimension in the critical Sobolev space. From this, we finish the classification of the regularities for which this problem is well-posed or ill-posed.